АДАПТИВНА СИСТЕМА КЕРУВАННЯ ПЕРЕТВОРЮВАЧЕМ ЧАСТОТИ НА ОСНОВІ РЕЗОНАНСНОГО ІНВЕРТОРА З НЕЛІНІЙНИМ РЕГУЛЮВАННЯМ - Павлов , Г.В.; Вінниченко, І.Л.; Покровський, М.В. (Інститут електродинаміки НАН України, Київ, 2018)
The adaptive microprocessor control system of the frequency converter based on the resonant inverter is developed, which allows, by implementing of the soft switching of power transistors, forming the low-frequency sinusoidal output voltage with low THD and, extending the operating range of the load characteristics of the converter due to the adaptive regulation. The corrected value of the relative output voltage, which is considered during the formation of the control pulses sequence, which goes to the key elements of the circuit, during the escape from the operating range of the load characteristics of the converter, is determined. References 8, figures 3.